Pengaruh Luas Lahan dan Pupuk Bersubsidi Terhadap Produksi Padi Nasional - Agung Budi Santoso (Jurnal Ilmu Pertanian Indonesia, 2015)
Rice has become a staple food of Indonesia's population. The target of rice self-sufficiency continued to be a priority of the government until 2017. This study aims to analyze land use and subsidized fertilizer that affect national rice production and analysis description of the factors that affect rice production covering the spread and proportion in each of the major islands in Indonesia. The data used in this study was a secondary data derived from agricultural statistics of 2013 issued by the Data Center and Information Ministry of Agriculture. The data was processed using multiple linear regression analysis. The results that the national rice production was affected by land use, realization of subsidized urea fertilizer, realization of subsidized SP-36 fertilizer, and realization of subsidized ZA fertilizer. All of these factors on rice production was inelastic in the short term or long term. Java and Bali Island have the highest proportion in all the factors that affect national rice production.